Functional joint center of prosthetic feet during level ground and incline walking. (July 2020) - Lecomte, Christophe; Starker, Felix; Guðnadóttir, Elísabet Þ.; Rafnsdóttir, Særún; Guðmundsson, Kjartan; Briem, Kristin; Brynjolfsson, Sigurður
Highlights: Ankle functional joint center location varies between different prosthetic feet. The position of functional ankle joint was calculated using a roll over test machine. Functional joint center of prosthetic feet has a different location depending of walking tasks. A correlation can be established between gait analysis and machine testing. Abstract: Energy storage and returning prosthetic feet do not provide a well-defined articulation point compared to the human ankle. Calculation of user relevant parameters, such as ankle power, requires such a joint center point when using traditional mechanical models. However, shortcomings of current calculation methods result in some errors. The aim of this case study was to compare conventional ankle joint calculations to a functional joint center (FJC) using data collected on a roll-over test machine and in a motion lab during dissimilar walking tasks. Three prosthetic feet were evaluated on a roll-over test machine . Then, two trans-tibial amputees were each fitted with the same three prosthetic feet matching their weight and activity category. Kinematic data were collected during walking on level ground, as well as up and down a slope. The FJC during the stance phase of gait was calculated for each test method and compared with outcomes using conventional methods. The location of the FJC was generally anterior and inferior to the estimated anatomical joint position. Importantly, the FJC location varied for the different prosthetic feet and was task dependent as per the three gait conditions. This was reflected in different ankle angles and moments of FJC calculations compared to conventional methods for level ground walking. Differences in the calculated FJC between conditions represented the variations in prosthetic foot deformation, and explained how this parameter is influenced by the prosthetic's stiffness. For level ground walking, calculated FJC location between human subject testing and machine evaluation were strongly correlated. Both stiffness and task dependent demands of the prosthetic foot should be considered during testing. The FJC of elastic ankles can serve as a parameter for characterization and differentiation between various prosthetic foot designs and be an important parameter for prosthetic foot designers to consider. As the position of the FJC is dependent on the design and task, it is a more informative measure of the prosthetic foot's response to the user's needs. Furthermore, prosthetists could use this metric in clinical practice to better appreciate amputee feedback and perception. FJC provides an alternative center during calculation of ankle power using standard methods.